148k views
5 votes
Which is the simplified form of the expression?

Which is the simplified form of the expression?-example-1
Which is the simplified form of the expression?-example-1
Which is the simplified form of the expression?-example-2
Which is the simplified form of the expression?-example-3
Which is the simplified form of the expression?-example-4
Which is the simplified form of the expression?-example-5
User Otm
by
5.2k points

1 Answer

3 votes

Answer:

1 / q^30.

Explanation:

[(p^2)(q^5)]^-4 * [(p^-4)(q^5)]^-2

Using the law (a^b)^c = a^bc :-

= p^-8 * q^-20 * p^8 * q^-10

= p^(-8+8) * q^(-20-10)

= p^0 * q^-30

= 1 * q^-30.

= 1 / q^30.

User Peddy
by
5.5k points